Apocalyptic thought in late medieval England, c. 1350 to c. 1425 - Cox, Eleanor (2024)
This thesis examines how apocalyptic thought was understood, interpreted and portrayed in late-medieval England. Apocalypticism in this area and time has been under explored compared to on the continent, where responses to anxieties regarding the end of time resulted in violence. In addressing this historiographical gap, this thesis draws on a multitude of source materials, including biblical commentaries, prophecies, illuminations, wall paintings, stonework, and stained glass. The thesis considers a series of case studies which reveal a variety of experiences and engagements with apocalyptic thought.